2017
DOI: 10.1136/bmjopen-2016-011781
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in birth weight and body mass index during infancy through age 7 years: a study within the Danish National Birth Cohort

Abstract: BackgroundSocioeconomic inequalities in birth weight and in body mass index (BMI) later in childhood are in opposite directions, which raises questions about when during childhood the change in direction happens. We examined how maternal and paternal education and household income were associated with birthweight z-scores and with BMI z-scores at age 5 and 12 months and 7 years, and we examined the socioeconomic differences in the tracking of these z-scores across infancy and childhood.MethodsThe associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
4
21
1
Order By: Relevance
“…Parental education is associated with BMI after early childhood, which parallels previous population based studies showing no association ( 29 ) or lower BMI ( 30 ) in the offspring of mothers with lower education before two years of age but a clear inverse correlation between the BMI of offspring and maternal education after four years of age. In early childhood, the lack of association between parental education and offspring BMI might be due to low birth weight associated with low parental education affecting BMI over the first years ( 29 ). Nevertheless, it may also reflect a change in the genetic architecture of BMI.…”
Section: Discussionsupporting
confidence: 87%
“…Parental education is associated with BMI after early childhood, which parallels previous population based studies showing no association ( 29 ) or lower BMI ( 30 ) in the offspring of mothers with lower education before two years of age but a clear inverse correlation between the BMI of offspring and maternal education after four years of age. In early childhood, the lack of association between parental education and offspring BMI might be due to low birth weight associated with low parental education affecting BMI over the first years ( 29 ). Nevertheless, it may also reflect a change in the genetic architecture of BMI.…”
Section: Discussionsupporting
confidence: 87%
“…The associations between low maternal education level and more rapid infant weight gain in the first 6 months could largely be explained by shorter gestational age, and smaller weight for gestational age z-score. In line with previous studies, [ 36 39 ] our study found that infants with lower educated mothers had shorter gestational age, and had smaller weight for gestational age z -score. Weight gain during the first few months after birth is highly dependent on birth weight, since babies born with a smaller size tend to catch-up, while heavier babies tend to catch-down.…”
Section: Discussionsupporting
confidence: 93%
“…On another note, several maternal parameters could be indirectly contributing to child overweight and obesity and risk of chronic disease. Firstly, pre-pregnancy maternal BMI could be contributing to the increased birthweights of infants, which may be persist into childhood and adulthood as overweight [69][70][71]. Moreover, there is an association between a Caesarean delivery and higher incidence of overweight and chronic disease for the children [72,73].…”
Section: Discussionmentioning
confidence: 99%